Pemberdayaan Masyarakat melalui Perpustakaan Desa Berbasis Inklusi Sosial (Studi Kasus Perpustakaan â€œSumber Ilmuâ€ Desa Marga Sakti Kabupaten Musirawas) - Mustika Diana; Yanto Yanto; Redi Pirmansyah (Tik Ilmeu: Jurnal Ilmu Perpustakaan dan Informasi)
Libraries can play a more role and can contribute in terms of community empowerment, closer, invite and empower the community. One way to get closer to the community is that the library can use the concept of inclusion to achieve its goals as a principle of lifelong learning. Inclusion-based libraries are libraries that facilitate the community in developing their potential by seeing cultural diversity, willingness to accept change, and offering opportunities to try, protect and fight for culture and human rights. This has been done by the Library of Science Resources in Marga Sakti Village, Musi Rawas Regency, with the concept of a Village Library Based on Social Inclusion, which has made the library an institution that can empower the community through productive activities such as making bitter melon chips, cultivating crickets, providing internet access for the community, Karang Taruna activities by establishing Youth Bands, PKK activities centered in libraries, storytelling activities, mobile libraries, establishing reading villages and others. Of the many activities above, this indicates that the library has become the central activity of the village community and as a concrete manifestation that the Marga Sakti Village Resource Library has implemented the concept of Social Inclusion.